Towards an institutional setup for industrial policy in late industrialization in the 21st century - Jan Grumiller; Werner G. Raza (Austrian Foundation for Development Research (ÖFSE), 2019)
Political and scholarly debates on the potentials and constraints of inclusive and sustainable development in the global periphery are at the core of the developmental discourse. This paper argues that discussions on the effectiveness, inclusiveness and sustainability of economic development need to take the political economic contexts of specific peripheral countries into account. The paper highlights that the more recent literature related to the developmental state debate provides valuable insights to this end, but needs (i) further conceptual extension, in particular with respect to the role of social inclusion and hegemony, and (ii) operationalization in order to be useful from a policy perspective. This paper aims to add to these two gaps in the literature.
Keywords: 330; developmental state; institutional regime; hegemony; inclusiveness; strategic relational approach